"Beat the Shock Clock": An Interprofessional Team Improves Pediatric Septic Shock Care. (June 2016) - Tuuri, Rachel E.; Gehrig, Madeline G.; Busch, Carrie E.; Ebeling, Myla; Morella, Kristen; Hunt, Lisa; Russell, W. Scott
Ideal care for septic shock (SS) is difficult. This interprofessional quality improvement intervention in a mid-volume pediatric emergency department aimed to reduce time to vascular access, fluid resuscitation, and antibiotics for SS. Intensive education, a care pathway, and an order set were applied. Outcome measures for patients with criteria for SS before and after intervention were compared. There were 43 patients pre-intervention (January 2009 to June 2011) and 63 post-intervention (June 2012 to June 2013). Median time to vascular access decreased from 37 minutes pre-intervention to 24 minutes post-intervention ( p = 0.05). Median time to first fluid bolus decreased from 35 to 26 minutes ( p = 0.08). Percentage of boluses delivered rapidly by pressure method increased from 21% to 74% ( p < 0.0001). Median time to antibiotics decreased from 92 to 55 minutes ( p = 0.02). In conclusion, a multimodal, interprofessional quality improvement intervention in a mid-sized pediatric emergency department improved the time to critical interventions for SS.